Fenntartható (lét)fejlődés, avagy egy új erkölcs hajnala? Morális terhek Gelencsér András Ábrándok bűvöletében című könyve mentén - Laki, Beáta (Kultúratudományi Szemle, 2024)
Sustainable development(of existence) or the dawn of a new morality? :Moral burdens along the lines of András Gelencsér's book "Ábrándok bűvöletében" Humanity's path to environmental disaster became clear in the second half of the 20th century. According to the information available at the time, it was high time to initiate and implement significant changes, not least at the global level, to avoid the predictions of the less-than-ideal future. I intend to discuss all this in the spring of 2023, in the context of a paper written on an (obviously) electricity-powered computer, and also what moral duties and responsibilities we may have at the level of the individual, the community, and humanity as a whole, and why. Where can our consumerist social behaviour, still most prevalent today, lead us? What are the other factors that play a role in the continuing exploitation of nature? But, without wishing to be exhaustive, I also highlight, through a few examples, the possibilities and good practices that we can find in our present day, which do not use the environment around us as a tool but try to live in a kind of symbiotic relationship with it. The subject is not new, but it is a huge one. The solutions proposed are not particularly revolutionary, but by adding new perspectives to the chemical engineer and air chemist András Gelencsér's sobering book, my study seeks to open up further perspectives on environmental dilemmas, framed in terms of energy needs and available raw materials.